Modernisation des réseaux dans le Mexique révolutionnaire et postrévolutionnaire. Marcelo Portillo, entre communauté paysanne et parti politique - Évelyne Sanchez (Caravelle)
From the path of a local actor in the Mexican Revolution, the article analyzes the impact of the emerging social structures linked to the revolution –agrarians groups and political parties– to understand the specific mechanisms of irruption of modernity within the villages. This case shows the contradictions between the revolutionary project that sought to defend the traditional organization of communities and accelerated forms of sociability of modernization.